PENGARUH SISTEM OLAH TANAH DAN PEMUPUKAN NITROGEN JANGKA PANJANG TERHADAP RESPIRASI TANAH DI LAHAN POLITEKNIK NEGERI LAMPUNG TAHUN TANAM KE-27 - Erdiana Damayanti; Muhajir Utomo; Ainin Niswati; Henrie Buchari (Jurnal Agrotek Tropika, 2020)
Unsustainable cultivation techniques can cause carbon loss on farm. The cultivation technique that is often used by farmers today is intensive tillage. Intensive tillage can increase CO2. Steps to reduce CO2 gas emissions, while increasing carbon stored in the soil by implementing agricultural cultivation with conservation tillage system (Olah Tanah Konservasi). The conservation tillage system is able to reduce global warming through absorption of C in the soil, and reduce CO2 emissions. In addition, fertilization can also affect CO2 emissions. CO2 emissions in the soil come from soil respiration. The purpose of this study was to determine the effect of long-term tillage systems on soil respiration, determine the effect of long-term N fertilization on soil respiration, and determine the effect of interactions between tillage systems and long-term N fertilization on soil respiration. The study was arranged in a randomized block design (RBD) consisting of two factors, namely the tillage system and nitrogen fertilization factors. The first factor is the treatment of tillage system (T) namely T0 = no tillage, and T1 = intensive tillage, while the second factor is without nitrogen fertilizer (N0) and high nitrogen fertilizer (N1). The data obtained will be tested for homogeneity by Bartlett Test and additives tested by Tukey Test. Furthermore, the data were analyzed by analysis of variance and continued with a BNJ test of 5% level. Observation of soil respiration was done 4 times, namely -1, 1, 2, 3 days after tillage. The results showed that soil respiration one day before to three days after the soil was treated in intensive tillage (OTI) was the same as the no tillage system (TOT), soil respiration -1 days after tillage to 3 days after tillage on nitrogen fertilization (100 N kg ha-1 ) given in the previous planting season the same as without fertilization (0 kg N ha-1), and there is no interaction between the tillage system and nitrogen fertilization on soil respiration.